Practical design considerations for high speed digital board - Kyaw, Soe Moe. (2010)
This report presents the development of a mock up electronic system, High Speed Digital Board (HSDB), which is used to validate the design rules developed through previous final year projects. Therefore, some improvements in printed circuit board (PCB) layout and routing based on previous projects are presented. The results from the improvements are presented and discussed after the development of firmware, assembly and functional testing.